Application of carboxymethyl cellulose sodium (CMCNa) in maize–wheat cropping system (MWCS) in coastal saline-alkali soil - Li, Ge; Shan, Yuyang; Nie, Weibo; Sun, Yan; Su, Lijun; Mu, Weiyi; Qu, Zhi; Yang, Ting; Wang, Quanjiu (The Science of the total environment, 2024)
Sodium carboxymethyl cellulose (CMCNa) application has been a promising approach to improve soil quality. The purpose of this study was to explore the effects of CMC-Na on soil infiltration, evaporation, water-salt distribution, crop growth, water use efficiency and net profit (Net) in a coastal saline-alkali soil maize–wheat cropping system (MWCS). Five CMC-Na application amounts (0, 0.1, 0.2, 0.4 and 0.6 g kg−1) were designed for the soil column experiment indoor, and five CMC-Na application amounts were used in 2019–2020 field experiment (CK: 0, C10: 10 kg ha−1, C20: 10 kg ha−1, C30: 10 kg ha−1 and C50: 10 kg ha−1), No treatment will be applied in 2021. The results showed that (1) CMC-Na treatment reduced soil cumulative infiltration, infiltration rate, daily evaporation, and cumulative evaporation. (2) After the application of CMCNa, the average soil water storage (SWS) in the 0–60 cm soil layer increased, and soil salinity (SSC) decreased in most treatments. (3) In the 2019–2020, the maize aboveground biomass (B), yield (Y) and water use efficiency (WUE) were the highest under the C20 and C30 treatments, which were 15.24 and 15.32 t ha−1, 5.67 and 5.49 t ha−1 and 1.74 and 1.52 kg ha−1 mm−1, respectively, and the wheat under C30 treatment is the highest, which were 10.98 t ha−1, 5.27 t ha−1 and 1.78 kg ha−1 mm−1. (4) A dose of 25.5 kg ha−1 and 38.9 kg ha−1 was recommended as the most optimal CMC-Na application for maize and wheat in coastal saline alkali soil, respectively. [Display omitted] •CMC-Na prevents soil water from infiltrating and reduces soil evaporation.•CMC-Na increased soil water storage and reduced soil salinity.•Excessive CMC-Na has negative impact on crops growth in saline-alkali soil.•25.5 kg ha−1 was recommended as an appropriate CMC-Na strategy for maize.•38.9 kg ha−1 was recommended as an appropriate CMC-Na strategy for wheat.